Copper(II) and nickel(II) uptake from aqueous solutions by cork wastes: a NMR and potentiometric study (Polyhedron, 2002)
Due to the increasing interest in the use of biomasses from agriculture as removing agents for heavy metals in waste effluents, we present here a joint potentiometric and 13C MAS and cross polarization-magic angle spinning NMR (CP-MAS NMR) study on cork interaction with Cu(II) and Ni(II). Through potentiometry we were able to distinguish two kind of interactions, a stronger one which involves protonated sites on cork and a second that allows hydroxide precipitation of the bound metal ion into the cork structure. NMR signal analysis suggests a specific metal complexation on the carbohydrate moieties of polymeric cork matrix. The 13C MAS NMR suggests that the dynamics in the MHz range and the overall arrangement of polymeric matrix is not affected by metal binding; and the spin relaxation times T1ρ(1H) and T1ρ(13C) show that no significant difference of relaxation processes in the KHz range is introduced by metal coordination.

Copper(II) and nickel(II) uptake from aqueous solutions by cork wastes: a NMR and potentiometric study - Villaescusa, Isabel; Fiol, Núria; Cristiani, Franco; Floris, Costantino; Lai, Simona; Nurchi, Valeria Marina (Polyhedron, 2002)
Due to the increasing interest in the use of biomasses from agriculture as removing agents for heavy metals in waste effluents, we present here a joint potentiometric and 13C MAS and cross polarization-magic angle spinning NMR (CP-MAS NMR) study on cork interaction with Cu(II) and Ni(II). Through potentiometry we were able to distinguish two kind of interactions, a stronger one which involves protonated sites on cork and a second that allows hydroxide precipitation of the bound metal ion into the cork structure. NMR signal analysis suggests a specific metal complexation on the carbohydrate moieties of polymeric cork matrix. The 13C MAS NMR suggests that the dynamics in the MHz range and the overall arrangement of polymeric matrix is not affected by metal binding; and the spin relaxation times T1ρ(1H) and T1ρ(13C) show that no significant difference of relaxation processes in the KHz range is introduced by metal coordination.
Keywords: copper; Cork; Metal uptake; Nickel; Potentiometric titration; Solid state 13C MAS and CP-MAS NMR